CD21−/low B cells associate with joint damage in rheumatoid arthritis patients. (17th June 2019) - Thorarinsdottir, Katrin; Camponeschi, Alessandro; Jonsson, Charlotte; Granhagen Önnheim, Karin; Nilsson, Jenny; Forslind, Kristina; Visentini, Marcella; Jacobsson, Lennart; Mårtensson, Inga‐Lill; Gjertsson, Inger
Abstract: Depletion of B cells is beneficial in rheumatoid arthritis (RA) patients with autoantibodies to citrullinated proteins (ACPA) and/or the Fc portion of immunoglobulins (rheumatoid factor [RF]), suggesting a role for B cells in disease pathogenesis. To date, however, the identity of specifically pathogenic B cell subsets has not been discovered. One candidate population is identified by the low expression or absence of complement receptor 2 (CD21 −/low B cells). In this study, we sought to determine whether there was any correlation between CD21 −/low B cells and clinical outcome in patients with established RA, either ACPA + /RF + (n = 27) or ACPA − /RF − (n = 10). Healthy donors (n = 17) were included as controls. The proportion of the CD21 −/low CD27 − IgD − memory B cell subset in peripheral blood (PB) was significantly increased in ACPA + /RF + RA patients compared with healthy donors, and the frequency of this subset correlated with joint destruction ( r = 0.57, P < 0.04). The levels of the chemokines CXCL‐9 and CXCL‐10 were higher in synovial fluid than in plasma, and PB CD21 −/low cells expressed the receptor, CXCR3. In synovial fluid, most of the B cells were CD21 −/low, approximately 40% of that population was CD27 − IgD −, and a third of those expressed the pro‐osteoclastogenic factor receptor activator of the nuclear factor κB ligand (RANKL). This subset also secreted RANKL, in addition to other factors such as IL‐6, even in the absence of stimulation. We interpret these data as reason to propose the hypothesis that the CD27 − IgD − subset of CD21 −/low B cells may mediate joint destruction in patients with ACPA + /RF + RA.